Control of uninterruptible power supply system with minimization of fuel consumption - Pichkalev, E.S.; Yamnenko, Yu.S. (Технічна електродинаміка, 2012)
Conditions to minimize fuel consumption in uninterruptible power supply with diesel generator at variable load are obtained. Estimation of fuel consumption at acceleration and braking stages of diesel generator was executed taking into account the cost of battery charge. Minimization of fuel consumption required for the transition process is achieved by adjusting the position of the fuel valves. Minimization of fuel consumption is shown for diesel generator HATZ 1D90-Supra.